2015
DOI: 10.1002/rnc.3457
|View full text |Cite
|
Sign up to set email alerts
|

Geometric modeling and local controllability of a spherical mobile robot actuated by an internal pendulum

Abstract: SUMMARYIn this paper, we present the modeling and local equilibrium controllability analysis of a spherical robot. The robot consists of a spherical shell that is internally actuated by a pendulum mechanism. The rolling motion of the sphere manifests itself as a nonholonomic constraint in the modeling. We derive the dynamic model of the system using Lagrangian reduction and the variational principle. We first compute the Lagrangian and identify the symmetry with respect to a group action. The system Lagrangian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…More recently, [13] provides a detailed analysis of the trajectory of the Chaplygin sphere's contact point, and it has been shown that the dynamics of the Chaplygin top exhibit a strange attractor [14] and the phenomenon of reversal [15]. The dynamics of the rolling ball with dynamic internal structure is also an active topic in the nonholonomic mechanics literature [16,17,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [13] provides a detailed analysis of the trajectory of the Chaplygin sphere's contact point, and it has been shown that the dynamics of the Chaplygin top exhibit a strange attractor [14] and the phenomenon of reversal [15]. The dynamics of the rolling ball with dynamic internal structure is also an active topic in the nonholonomic mechanics literature [16,17,7,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…where ξ ∈ R 2n+2 and ν ∈ R n+2+c , c ∈ {0, 1, 2}, are constant Lagrange multiplier vectors enforcing the initial and final conditions, (3.7) and (3.8), respectively. The Hamiltonian is 20) where λ ∈ R 2n+2 is a time-varying Lagrange multiplier vector enforcing the dynamics (3.6). Recall from (2.22) that the function describing the uncontrolled equation of motion for the rolling disk is κ (t, x, u) ≡ −rFe,1 + n i=0 miKi d2 + n i=0 mi (r sin φ + ζi,1) 2 + (r cos φ + ζi,3) 2 ,…”
Section: Controlled Equations Of Motion For the Rolling Diskmentioning
confidence: 99%
“…More recently, [12] provides a detailed analysis of the trajectory of the Chaplygin sphere's contact point, and it has been shown that the dynamics of the Chaplygin top exhibit a strange attractor [13] and the phenomenon of reversal [14]. The dynamics of the rolling ball with dynamic internal structure is also an active topic in the nonholonomic mechanics literature [15,16,6,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations